Systematic review on the frequency of occurrence in nerve branches and the side of the face involved in trigeminal neuralgia and its clinical implication - Teshome, Assefa Agegnehu; Walle Ayehu, Gashaw; Ashagrie, Berhanu Kindu; Baye, Nega Dagnaw; Ayenew, Atalo Agemas; Mengstie, Misganaw Asmamaw; Yazie, Taklo Simeneh; Gebeyehu, Asaye Alamneh; Sisay Chanie, Ermias; Molla, Yalew Melkamu; Taye Jemberie, Molla; Abate, Agmas Wassie (Frontiers in Neurology, 2024)
Purpose The purpose of this systematic review is to answer the focused question, “What is the commonly affected nerve branch and the side of the face involved in trigeminal neuralgia?” Types of studies reviewed This systematic review included studies reporting commonly affected trigeminal nerve branches and the side of the face involved in trigeminal neuralgia. To find the potential studies published, the authors utilized specific search databases such as PubMed, and Google scholar. Results Among 132 published studies, the authors selected only 11 to be included for this systematic review. The sample size ranged from 50 to 43,518 study subjects. This review identified that the mandibular branches of the trigeminal nerve were the most affected, followed by the maxillary branch. The review also identified that the right side of the face was predominantly affected. Conclusion and practical implications The authors of this review identified a higher occurrence of trigeminal neuralgia in the mandibular division of the nerve, commonly affected on the right side of the face. Further prospective-based research and meta-analysis are required to validate the commonly occurring trigeminal nerve branch and sidedness of the face involved with its clinical implications in trigeminal neuralgia.